UV-activated multilayer nanomatrix provides one-step tunable carbohydrate structural characterization in MALDI-MS1. Issue 8 (14th August 2015) - Obena, Rofeamor P.; Tseng, Mei-Chun; Primadona, Indah; Hsiao, Jun; Li, I-Che; Capangpangan, Rey Y.; Lu, Hsiu-Fong; Li, Wan-Sheung; Chao, Ito; Lin, Chun-Cheng; Chen, Yu-Ju
<x xml:space="preserve">Abstract</x> Our work highlights DHB@MNP-induced pseudo-MS/MS for oligosaccharide characterization, with some insights on this nanoparticle-mediated energy transfer dynamics.